Discovering media literacy : teaching digital media and popular culture in elementary school - Hobbs, Renee (Corwin, a Sage Company, 2013)
"Many professional books talk about digital and media literacy, but this text addresses the complete continuum' from television to technology' and guides teachers to think deeply about their own preferences and beliefs, as well as those of their students to develop knowledgeable, informed media users and consumers for the 21st Century." ' Kristin Ziemke Fastabend, First Grade Teacher Chicago Public Schools Give digital kids a voice! Today' s kids are digital natives, but what' s the best way to help them become ...